Efficiency evaluation of HRF mechanism on EDoS attacks in cloud computing services. (27th June 2022) - Ganiya, Rajendra Kumar; Veeraiah, D.; Bulla, Suneetha; Rao, J. Nageswara; Deol, G.J. Sunny
The conventional DDoS assaults can be transformed into an economic denial of sustainability (EDoS) assaults because of elasticity in the cloud services. This EDoS attacks use the cloud assets for creating administration inaccessibility to the clients. There is a mandate to diminish EDoS assaults. HRF is the most suitable and an effective mechanism to identify and diminish such assaults, in which assailant requests are recognised and dropped preceding arriving at the web server. This paper assesses and examines the cost and performance sway using queuing theory and assess experimental model in terms of key performance metrics which incorporate QoS and cost metrics. Different scenarios appropriate to HRF mechanism are taken into consideration and examined. Performance is compared with existing approaches using game theoretical methodology. To get the systematic solution and calculation of game value, various probabilities of defending techniques and assaulting strategies through numerical outlines are done. Lastly conclusions are drawn.